Significance of Buongiorno’s model on viscoelastic MHD flow over a heated lubricated surface subject to Joule heating - Sarfraz, Mahnoor; Khan, Masood; Ullah, Malik Zaka; Abuzaid, Dina (International journal of modern physics. B, Condensed matter physics, statistical physics, applied physics, 2023)
Lubrication theory has attained attention lately due to its practical applications, such as the formation of thin films, adhesives, and lubrication of components of machines. Jeffrey’s nanofluid flow over the stagnation region past a power-law lubricated surface is presented in this study. Buongiorno’s model is employed to scrutinize the effects of thermophoresis and Brownian motion phenomena with constant wall and prescribed surface temperature (PST) and effects of heat source/sink, chemical reaction, and Joule heating. Due to the continuity of shear stress of fluid-lubricant and velocity at the interface, interfacial conditions are generated. By similarity conversions, ordinary differential equations are obtained and their solutions are computed numerically. For power-law index equaling 1 2 , local similarity solutions are calculated by adopting a finite difference scheme, viz. bvp4c in MATLAB. The energy profiles for constant and prescribed temperatures are monitored. The effects of pertinent parameters on the flow, thermal, and mass distributions are scrutinized and illustrated in graphs. Flow field decreases significantly by raising slip parameter as the aptitude of power-law lubricant to improve the velocity of the bulk fluid. The numerical comparison of wall stress and Nusselt number is also presented. The slip and Jeffrey’s material parameters raise the numerical outcomes of the wall shear stress. In addition, increment in Prandtl number enhances the numerical value of the Nusselt number; however, it reduces for relaxation-to-retardation times ratio.